1986
DOI: 10.1073/pnas.83.1.14
|View full text |Cite
|
Sign up to set email alerts
|

L-Canavanine and protein synthesis in the tobacco hornworm Manduca sexta.

Abstract: L-Canavanine, a nonprotein amino acid of certain leguminous plants, manifests potent Insecticidal properties in a canavanine-sensitive insect such as the tobacco hornworm Manduca sexta (L.) (Sphingidae). This arginine analog is activated and aminoacylated by arglnyl-tRNA synthetase and incorporated into nascent polypeptide chains to create structurally aberrant, canavanine-containing proteins.Analysis ofincorporation of [3H]leucine into protein inM. sexta larvae that had been injected with canavanine revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Selenocysteine, while not one of the 20 amino acids normally identified as a protein constituent, is found in approximately 25 human proteins, largely those involved in redox reactions (Nauser et al 2012) and is now considered the 21st proteinogenic amino acid. Similarly, canavanine, an arginine analogue and plant non-protein amino acid, is incorporated into proteins by pests that feed on the plant tissues (Rosenthal and Dahlman 1986;Huang et al 2011). In each of these cases, the amino acid that was substituted into protein for another, such as canavanine for arginine, is structurally quite similar to the original (Melangeli et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Selenocysteine, while not one of the 20 amino acids normally identified as a protein constituent, is found in approximately 25 human proteins, largely those involved in redox reactions (Nauser et al 2012) and is now considered the 21st proteinogenic amino acid. Similarly, canavanine, an arginine analogue and plant non-protein amino acid, is incorporated into proteins by pests that feed on the plant tissues (Rosenthal and Dahlman 1986;Huang et al 2011). In each of these cases, the amino acid that was substituted into protein for another, such as canavanine for arginine, is structurally quite similar to the original (Melangeli et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Another C 5 NPAA dencichine found in all parts of Lathyrus sativus and cycads is a neurotoxin to higher animals (Xie et al 2007) and has been shown to be the causative principle of the motor neuron disease, lathyrism (Campbell et al 1994). Canavanine (C 5 ) is synthetised in many leguminous plants and plays a seminal role in plant chemical defence against insects (Rosenthal and Dahlman 1986). Canavanine was also found to inhibit plant growth (Nakajima et al 2001).…”
Section: Role In Plant Defencementioning
confidence: 98%
“…In order to address whether both biosensors developed in this study specifically detect DNA-damaging agents, we tested the wellcharacterized non-genotoxic antibiotic canavanine (Rosenthal and Dahlman, 1986). Remarkably, neither biosensor responded to canavanine regardless of the strain background or whether the doses were toxic to the cells.…”
Section: Biosensor Sensitivity To Non-genotoxic Agentsmentioning
confidence: 99%